2014
DOI: 10.1111/wvn.12047
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Measure to Assess Healthcare Providers’ Implementation of Patient‐Centered Care

Abstract: The PCC measure demonstrated acceptable psychometric properties. The low variance in responses, which is anticipated for instruments assessing fidelity of intervention implementation, accounts for the low reliability coefficients. Additional testing of the measure's psychometric properties in different groups of healthcare providers is warranted. The measure can be used to monitor healthcare providers' implementation of PCC in their usual practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 28 publications
0
41
0
Order By: Relevance
“…One study shows that HCPs who perform least well in external assessments tend to overrate their own performance [48]. Other studies have found that self-assessment of person-centered methods was essential for continuing education to promote professional growth, integration of theory into practice, and critical thinking [49]. In particular, self-assessment was found to have a greater impact on the process of self-reflection and was associated with a more positive or meaningful learning experience [50].…”
Section: Discussionmentioning
confidence: 99%
“…One study shows that HCPs who perform least well in external assessments tend to overrate their own performance [48]. Other studies have found that self-assessment of person-centered methods was essential for continuing education to promote professional growth, integration of theory into practice, and critical thinking [49]. In particular, self-assessment was found to have a greater impact on the process of self-reflection and was associated with a more positive or meaningful learning experience [50].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, nurses need to know and research the requirements, dislikes and likes of their clients, their values, capabilities, their nature of assistance and their needs for assistance in relation to their historical background (Thompson, Heath, & Mills, 2013). This attitude of collaboration will allow nurses and other health professionals to assist patients make informed decisions about their health direction without prejudice (D. Brown, McWilliam, & Ward-Griffin, 2006;Hudon, Fortin, Haggerty, Lambert, & Poitras, 2011;Sidani et al, 2014). Other researchers, however, have found a contrary thinking to PCC, arguing that it is a vague and poorly conceptualized principle (DiGioia III, Lorenz, Greenhouse, Bertoty, & Rocks, 2010;Laschinger, Heather, Gilbert, Lesley, & Leslie, 2010;Smith, Dewar, Pullin, & Tocher, 2010).…”
Section: Background and Significantmentioning
confidence: 99%
“…Validated measures of patient-centred care4 and interprofessional care3 provide new knowledge and should be included in formal education to enhance clinician knowledge and self-reflection. Organisations must explore innovative models of care that enhance care continuity.…”
Section: Commentarymentioning
confidence: 99%